1994
DOI: 10.1159/000227385
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Production of lnterleukin-8 by Human Lung Cancer Cells and Its Augmentation by Tumor Necrosis Factor Alpha and lnterleukin-1 at Protein and mRNA Levels

Abstract: A cell-to-cell interaction between tumors and host inflammatory cells is important for the subsequent cancer progression or regression. We examined the expression of interleukin-8 (IL-8) mRNAs by 9 human lung cancer cell lines and the influences of cytokines on IL-8 production and its gene expression. Substantial expressions of IL-8 gene were detected in 3 lung cancer cell lines (RERF-LC-OK, Lu-134-A-H, YO-88 cells). Moreover, 4 lung cancer cell lines (RERF-LC-MS, RERF-LC-OK, A549 and YO-88) were used to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Compared with normal lung tissue, increased quantities of IL-8 were detected in bronchogenic carcinoma tissue [5]. IL-8 is also spontaneously produced by human lung cancer cells, suggesting that tumor-derived IL-8 may be important in recruiting inflammatory neutrophils and promoting interaction between lung cancer and inflammatory cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal lung tissue, increased quantities of IL-8 were detected in bronchogenic carcinoma tissue [5]. IL-8 is also spontaneously produced by human lung cancer cells, suggesting that tumor-derived IL-8 may be important in recruiting inflammatory neutrophils and promoting interaction between lung cancer and inflammatory cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…YM98 and JT99 were established from malignant pleural effusion due to lung adenocarcinoma in our laboratory as described previously. 26) Patients. Sixty-five patients with pleural effusion were examined in Tokushima University Hospital after having obtained informed consent, as described previously.…”
Section: )mentioning
confidence: 99%
“…High level production of cytokines was reported in some malignant cell lines such as glioblastoma of the brain (21), multiple myeloma (8), uterine cervical cancer (10), renal cell carcinoma (13), bladder carcinoma (14), and lung cancer (15). Woodworth et al showed high level cytokine secretion from normal cervical keratinocytes and reduced productivity of cytokines in the HPV-immortalized cell lines and cervical cancer cell lines in vitro (25).…”
Section: Discussionmentioning
confidence: 99%